NURSING CARE FOR MENTAL HEALTH CLIENTS WITH SENSORY PERCEPTION DISTURBANCES: VISUAL HALLUCINATIONS IN MR. P WITH A FOCUS ON TALKING THERAPY INTERVENTION AT DR. RM SOEDJARWADI MENTAL HOSPITAL, KLATEN - Okti Isna Farihatin; Puspasari, Fida Dyah; Sudiarto, Sudiarto (PT. Jurnal Center Indonesia Publisher, 2025)
Background : Mental disorders are conditions in which individuals experience disturbances in psychological, social, and biological functions. One of the most common symptoms in patients with schizophrenia is visual hallucination, which refers to the perception of seeing something that does not actually exist. This condition affects the patient’s ability to function and interact with their social environment. Appropriate nursing interventions are required to help patients manage their hallucinations. One such intervention is the talking technique, a distraction strategy that redirects the patient’s attention from hallucinations to real-life interaction. Objective : This study aims to determine the process of mental nursing care for patients with sensory perception disorders: visual hallucinations with a focus on conversation interventions at Dr. Soedjarwadi Klaten Regional Hospital. Method : The design of this study uses a case study method consisting of stages of assessment, determination of nursing diagnosis, planning, implementation, and evaluation. The subject in this study was Mr. P, a patient at the Dr. RM Soedjarwadi Klaten Regional Mental Hospital. Results : The results of the study showed that consistent implementation of conversational strategies during treatment can reduce the intensity of hallucinations, increase awareness of reality, and rebuild patients' social interaction abilities. Counclusion : Conversation intervention is an effective approach in treating visual hallucinations in mental disorders patients.